Global trends and prospects for the development of gastronomic tourism in Ukraine and Odesa region - Oliinyk, Valentyna (Human Geography Journal, 2026)
The article examines current trends in the global development of gastronomic tourism, examines the potential of gastronomy in the Odessa region, and identifies non-dimensional territorial development of tourism in the administrative districts of the region. The purpose of the article is to analyze the potential and organization of gastronomic tourism in the Odessa region and proposals for its stimulation and intensification in peripheral locations of the region. Methods of territorial and statistical analysis, synthesis, and generalization are used to study and achieve the goal of the work. According to the results of the research, the offers of food tours of Ukrainian tourist enterprises are analyzed, the features of gatronomic tourism, the main directions of reorientation of the industry in modern conditions are highlighted, namely: the use of the domestic market, orientation to local products, holding various events, including gastronomic ones. A SWOT analysis of the tourist potential of gastronomic tourism in the Odessa region was compiled, directions for reorientation of gastronomic tourism for its activation were proposed, the author's gastronomic tour was developed, and prospects for the development of gastronomic tourism in the region were determined.Thus, the development of tourist destinations will contribute to solving social, cultural, economic and environmental challenges.  Gastronomic tourism is considered as one of the possible strategic directions for the development of the economy, the preservation of traditional economy, cultural heritage, and should also be a factor in the sustainable development of communities. The promotion and positive growth of demand for gastronomic tourism has every reason, because the country has a significant number of unique culinary customs, history, culture, in addition, the possibility of combining with other types of tourism, the use of the latest technologies and support from the government and local communities will strengthen the positive trends.